Stability switches induced by immune system boosting in an SIRS model with discrete and distributed delays - Barbarossa, Maria Vittoria; Polner, Mónika; Röst, Gergely (SIAM journal on applied mathematics, 2017)
We consider an epidemiological model that includes waning and boosting of immunity. Assuming that repeated exposure to the pathogen fully restores immunity, we derive an SIRS-type model with discrete and distributed delays. First we prove usual results, namely that if the basic reproduction number, R0, is less or equal than 1, then the disease-free equilibrium is globally asymptotically stable, whereas for R0>1 the disease persists in the population. The interesting features of boosting appear with respect to the endemic equilibrium, which can go through multiple stability switches by changing the key model parameters. We construct two-parameter stability charts, showing that increasing the delay can stabilize the positive equilibrium.